1996
DOI: 10.1242/jeb.199.8.1829
|View full text |Cite
|
Sign up to set email alerts
|

The Modulus of Elasticity of Equine Hoof Wall: Implications for the Mechanical Function of the Hoof

Abstract: During normal weight-bearing and locomotion, the equine hoof wall deforms in a consistent pattern; the proximal dorsal wall rotates caudo-ventrally about the distal dorsal border and there is latero-medial flaring posteriorly. The aim of this study is to examine whether there are regional differences in the modulus of elasticity of hoof wall material and whether such differences correlate with the pattern of deformation which occurs in vivo. The modulus of elasticity of equine hoof wall was determined in tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…23 Given the lateral location of the forelimb in relation to the center of a horse' s body, more loading could be expected at the medial quarter and toe. 24 Assuming that both sides of a hoof are morphologically similar and have similar elasticity, 25,26 the higher strains observed on the lateral side of the horses' hooves in the present study suggest that different forces act on each side. However, medial and lateral angles also affect strains in the hoof wall, with decreasing compression as the angle increases, particularly at the lateral side.…”
Section: Discussionmentioning
confidence: 59%
“…23 Given the lateral location of the forelimb in relation to the center of a horse' s body, more loading could be expected at the medial quarter and toe. 24 Assuming that both sides of a hoof are morphologically similar and have similar elasticity, 25,26 the higher strains observed on the lateral side of the horses' hooves in the present study suggest that different forces act on each side. However, medial and lateral angles also affect strains in the hoof wall, with decreasing compression as the angle increases, particularly at the lateral side.…”
Section: Discussionmentioning
confidence: 59%
“…Subtle differences in material properties among regions of the hoof result in variable responses to tensile [ 57 59 ] and compressive stresses [ 57 , 60 ]. Similar to shoe effects on P3 displacement, hoof capsule deformation also differed between laminitic and unaffected hooves.…”
Section: Discussionmentioning
confidence: 99%
“…It also suggests that the hoof wall behaves as an orthotropic material that resists compressive loads better than tensile stresses, and it confirms results of a study on material properties in which it was revealed that the Young modulus of the hoof horn is greater under compressive loads. 30 Although we did not evaluate laminar stresses in this study, it could be assumed that the strain concentration over the pillars as well as the significant increase in shear strain magnitudes following trimming could potentially induce focal disruptive stresses on the laminae. Conversely, providing that laminar integrity is sustained, increases in strains could stimulate growth and, therefore, thickness and strength of the hoof wall, resulting in healthier feet.…”
Section: Discussionmentioning
confidence: 99%